Regulatory barriers to the advancement of precision medicine. Issue 3 (3rd May 2016) - Pettitt, David; Smith, James; Meadows, Nick; Arshad, Zeeshaan; Schuh, Anna; DiGiusto, David; Bountra, Chas; Holländer, Georg; Barker, Richard; Brindley, David
ABSTRACT: Precision medicine utilizes tailored diagnostic, prognostic and therapeutic strategies based on an individual's molecular profile. Although it is gaining considerable traction and high-level political endorsement, it must overcome a number of translational hurdles, including regulatory barriers. At the core of precision medicine lies diagnostic tests and devices, however the regulatory classification of such products varies on a global basis. Navigating these convoluted regulatory pathways can be challenging – exacerbated by asymmetric technological advancement and regulatory progression. Both the EU and US are attempting to address such issues and newer concerns relating to direct-to-consumer testing. Flexible solutions are required to establish regulatory compliance across multiple countries and coordinated cross-collaboration initiatives need to empower technological development and globally harmonized regulation. The wider infrastructure, spanning beyond regulation, must also accommodate these changes and support subsequent clinical adoption, in order to firmly establish precision medicine in modern day medical practice.